NETIZENS' POLITENESS IN PRABOWO SUBIANTO'S INSTAGRAM COMMENT COLUMN "DURING A STATE VISIT TO QATAR" APRIL 13, 2025 - Indah Sardila; Rika Ningsih (SOSIOEDUKASI, 2026)
This research is motivated by a survey published by Kompas.com which states that the level of politeness of Indonesian netizens is the worst in Southeast Asia. The writer wants to find out more about whether it is true that such a level of politeness is true.  The problem in this study is how the politeness of netizens is contained in Prabowo Subianto's Instagram comment column. The purpose of this study is to explore and elaborate the politeness of netizens contained in Prabowo Subianto's Instagram comment column. Referring to the principle of Leech's politeness, this study uses a qualitative approach and content analysis method. The data in this study is in the form of all polite and impolite speech in Prabowo Subianto's Instagram comment column. In this study, the source of data is Prabowo Subianto's Instagram comment column on the post "During a State Visit to Qatar" The data collection technique is documentation, reading and recording techniques. The data analysis technique of this study uses the following Bungin content analysis techniques: Coding, data classification, analyzing and looking for relationships, and draft reports. Based on the results of the study, 80 data were obtained with the following details. The maxim of wisdom obtained 13 manners and 5 immodesties, the maxim of generosity obtained 7 manners and 0 immodesties, the maxim of praise obtained 17 manners and 0 immodesties, the maxim of humility obtained 5 manners and 7 immodesties, the maxim of agreement obtained 6 manners and 0 immodesty and the maxim of sympathy obtained 20 manners and 0 immodesties. Based on the details of the data above, it can be concluded that the politeness of netizens on Prabowo Subianto's Instagram is predominantly polite, it can be said to be polite because they appreciate and uphold respect for others, especially state leaders